Stigma Virginitas Terhadap Preferensi Memilih Pasangan Hidup di Kalangan Gen Z Surabaya - Effendi, Masitah; Fitri, Ananda Kurnia Wulan; A’yun, Qurrota; Saifullah, Muhammad Ilham (The Sociology of Islam, 2024)
Research on the preferences for choosing a partner in Generation Z examines changes in views regarding the value of virginity and virginity status which are undergoing transformation along with developments in time and technology. This research uses qualitative methods with a phenomenological approach and focuses on teenagers born from 1997 to 2012 and domiciled in Surabaya as the research population. This research uses a purposive sampling technique with data collection tools and methods using in-depth interviews supported by primary and secondary data. In general, it was found that Generation Z in Surabaya is looking for a comprehensive life partner by considering cognitive and emotional aspects. They also emphasized the importance of gender equality in romantic relationships, a focus on shared values, and the ability to work together to face life's challenges ahead.